Safety Detection and Assessment of Aqueduct Supporting Structure under Lateral Impact Load - LI Jun; CUI Dehao; YOU Ri; HAO Jie; PAN Wenming (Renmin Zhujiang)
In view of the structural damage of an aqueduct pile-pillar supporting structure caused by ship collisions,relevant engineering data were collected,and on-site detection and monitoring analysis were carried out.In addition,the finite element method was used to establish a three-dimensional entity analytical model of the aqueduct pile-pillar structure.Under the joint action of the coupled foundation and pile foundation and superstructure,numerical simulation and calculation analysis were carried out on the pile-pillar collision process.The distribution and characteristics of the damage of the supporting structure caused by collisions were studied and verified.The finite element numerical simulation results show that the high-stress area of the aqueduct pile-pillar structure during the ship collision process can be divided into two categories according to the cause.One is the high-stress area caused by the direct contact load,which occurs in the collision contact surface and the adjacent area between the ship in a collision and the bearing platform,and the other is caused by the overall bending deformation of the pile-pillar structure,which occurs in the dangerous section of the pile-pillar structure and the bearing platform connection.In addition,the simulation analysis and on-site detection results are consistent.By assessing the influence of ship collisions and checking the potential safety hazards of the aqueduct,the research results lay a foundation for the maintenance,reinforcement,and design of the aqueduct.